Level of job satisfaction amongst nurses in the North-West Province, South Africa: Post occupational specific dispensation - Sisinyana H. Khunou; Mashudu Davhana-Maselesele (AOSIS, 2016)
Background: Job satisfaction and burnout have been recurring problems amongst nurses in the Republic of South Africa (RSA). As a result, nurses are still leaving the rural public sector in search of lucrative work at the urban and private sectors and in developed countries. Accordingly, Occupational Specific Dispensation (OSD) was introduced as a strategy to ircumvent the problem. However, since the implementation of OSD in 2007, there have been no studies conducted regarding the level of job satisfaction amongst nurses after the implementation of OSD in the North-West Province, especially because each province has its own challenges that are unique to the area. Objectives: The study had two objectives: to describe the level of job satisfaction amongstprofessional and other category nurses (OCNs) at a public hospital in the North-West Provinceand describe the perceptions of nurses about OSD and their intention to continue working inthe hospital. Method: A quantitative descriptive cross-sectional design was used. Stratified random sampling was used to select a sample of 92 professional nurses (PNs), 90 enrolled nurses and enrolled nursing assistants (Nursing Act 2005), which made a total of 182 participants. For the purpose of the study, the enrolled nurses and enrolled nursing assistants were referred to as OCNs. Data were collected using the Minnesota Satisfaction Questionnaire-short form and OSD statements and analysed with Statistical Package for Social Science (SPSS, version 18). Results: The majority of PNs (79.3%, n = 73) and OCNs (86.7%, n = 77) were dissatisfied with the working conditions and salary: PNs (80.4%, n = 74) and OCNs (87.8%, n = 79). The nurses mostly discredited the current state of the OSD implementation. Majority of the PNs (84%, n = 77) and OCNs (91%, n = 82) disagreed with the statement that 'level of job satisfaction has improved after the implementation of OSD'. Conclusions: The National Department of Health should consider a holistic approach to address all work-related conditions for nurses in order to curb the attrition rates. Policy makers and unions should urgently review OSD for all categories of nurses.